2018
DOI: 10.15517/revenf.v0i35.31868
|View full text |Cite
|
Sign up to set email alerts
|

Internações hospitalares e impacto financeiro por tuberculose pulmonar na Bahia, Brasil

Abstract: Este estudo teve como objetivo descrever os casos de internações hospitalares e impacto financeiro da tuberculose pulmonar no estado da Bahia, Brasil, entre o período de 2012 e 2016. É um estudo epidemiológico, descritivo transversal, utilizando dados do Departamento de Ciência da Computação do Sistema Único de Saúde. As variáveis coletadas foram: sexo, faixa etária, valores dos serviços hospitalares e raça, relatadas no período de 2012 e 2016. Os casos de internações hospitalares foram selecionados de acordo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
1
2
0
9
Order By: Relevance
“…In Natal-RN, male subjects were those most often diagnosed with tuberculosis (69.5%). These results are similar to a study carried out in Caxias-MA, where of 570 patients, between 2006 and 2017, 65.6% were men [14], and in demonstrated agreement with a study developed by Souza Júnior et al (2018) [15] in which, during the years from 2012 to 2016, in the state of Bahia, the number of male patients with tuberculosis, accounting for about 70%, was twice as high as for females. In Montes Claros-MG, it was observed that of 661 patients with tuberculosis, 60.4% of the patients were male [16].…”
Section: Resultssupporting
confidence: 92%
“…In Natal-RN, male subjects were those most often diagnosed with tuberculosis (69.5%). These results are similar to a study carried out in Caxias-MA, where of 570 patients, between 2006 and 2017, 65.6% were men [14], and in demonstrated agreement with a study developed by Souza Júnior et al (2018) [15] in which, during the years from 2012 to 2016, in the state of Bahia, the number of male patients with tuberculosis, accounting for about 70%, was twice as high as for females. In Montes Claros-MG, it was observed that of 661 patients with tuberculosis, 60.4% of the patients were male [16].…”
Section: Resultssupporting
confidence: 92%
“…25 Note that the PC generated a financial impact of over R$ 126.6 million in the Northeast, according to table 4, significantly surpassing the kidney transplants performed in the region between 2013 and 2017. 26 It is reported, however, that the hospital costs for PC in Bahia observed in this study were higher than the hospitalization costs for Diabetes Mellitus (2013-2017) 27 and pulmonary tuberculosis (2012-2016) 28 recorded in the State.…”
Section: Discussionmentioning
confidence: 55%
“…Nessa perspectiva, o alto uso de recursos financeiros na prestação da assistência a nível hospitalar pelo SUS reflete a indispensabilidade de serviços de amparo direcionado à TP. Desse modo, a internação, o período de permanência, o atributo de exames de imagem e o Tratamento Diretamente Observado (TDO) resultam em um abalo orçamentário de grande expressividade no sistema de saúde (Souza Junior et al, 2018).…”
Section: Categorias1: a Visão Dos Custos Do Cliente Com Tuberculose Nunclassified
“…A tuberculose é vista como problema de saúde pública principalmente na população de níveis econômicos baixos na maioria dos países, tanto que se estima um terço no mundo e tem como microbiota causadora o Mycobacterium tuberculosis, mas em território nacional a incidência de notificação ainda é alta na população brasileira (Souza Junior et al, 2018;Silva et al, 2012).…”
Section: Introductionunclassified
See 1 more Smart Citation